Pengaruh Orientasi Kewirausahaan, Literasi Keuangan, dan Keunggulan Bersaing Terhadap Kinerja UKM Bisnis Keluarga - Mentari Ritonga; Sri Arita; Silvi Delfiani; Nita Sofia (Jurnal Ecogen, 2023)
Payakumbuh City makes UKM one of the businesses that support the lives of its people. It is proven that around 97% of the SME sector dominates business activities in Payakumbuh City. One of the factors that support the development of SMEs in Payakumbuh City is the strategic geographical location of the city of Payakumbuh, namely on the crossroad from Riau Province to West Sumatra Province. In recent years, Payakumbuh City tourist destinations have also developed rapidly. The development of tourist sites and the increase in the number of tourists visiting the city of Payakumbuh also impact the number of SMEs in the city of Payakumbuh. However, this threatens old SMEs in Payakumbuh City, especially family business SMEs that have been around for a long time. Many family business SMEs complain of difficulties in maintaining good business performance. A large number of new competitors with almost similar business products and the low ability of SMEs to innovate in the products they offer are suspected to be the substantial cause of the decline in the performance of family business SMEs in Payakumbuh City. The low knowledge and financial management skills of MSME actors exacerbate this phenomenon. Based on the problems faced by family business SMEs in Payakumbuh City, it is necessary to develop an effort to increase competitive advantage through various approaches, namely rising entrepreneurial orientation and financial literacy of family business SMEs in Payakumbuh City.Keyword : SMEs performance, family business, entrepreneurial orientation, financial literacy, competitive advantages